PELATIHAN DAN IMPLEMENTASI KONDISI FISIK BAGI PELATIH BULUTANGKIS KOTA PADANG - Eval Edmizal; Donie Donie; Vega Soniawan; Fella Maifitri (Universitas PGRI Palembang, 2019)
Badminton is an achievement sport that has complexity in training programs (locomotor and manipulative). Partners in this activity are PBSI Kota Padang. The problem faced is the coach's lack of a comprehensive understanding of the elements of physical condition and how to improve it for badminton athletes. An athlete should have a good physical condition in order to be able to realize techniques and apply tactics / strategies in play. This condition is one that triggers the low achievement of badminton athletes in the city of Padang. Solutions are given to improve the physical condition of athletes through training about the physical condition of badminton because physical conditions are needed in badminton. The target to be achieved is so that the trainer can understand the elements of physical condition and how to improve it as an effort to improve it. The output to be achieved is that the coach understands the elements of physical condition and how to improve it, especially badminton for badminton coaches throughout the city of Padang and the publication of scientific papers in journals. To achieve this, there are two methods used, first is by conducting field observations and collaborating with partners. The second stage is to provide training on physical conditions for the palatih in the city of Padang. The third stage evaluates the achievements made in these training activities